Peran Strategis Modal Ventura Dalam Ekosistem Kewirausahaan Digital - Tarigan, Afifah Sanu; Shafwan, Fatimah Ratu; Azhar, Alfiyyah; Setiawan, Ade; Syahwildan, Muhamad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Startups need a lot of capital to develop their business, especially in digitalization. Venture capital can be an important alternative option to assist startups as a source of funding in exchange for equity from the startup. Venture capital carries a relatively high risk because the company cannot withdraw the capital within a certain period. This article aims to explore the strategic role of venture capital in supporting the development of startups or SMEs. The research method used is qualitative with a descriptive approach related to the current conditions of the digital entrepreneurship ecosystem. This research is expected to contribute to the development of the digital entrepreneurship ecosystem with venture capital in Indonesia.